Poaching sources and trade routes in Peru and Ecuador warn of the unsustainable rural demand for preferred parrot species - Bermúdez Cavero, Alan Omar (2023)
Illegal wildlife trade remains highly active in the Neotropics, as indicated bythe thousands of parrots annually sold in illicit city markets. However, little isknown about where parrots are poached, whether certain parrot species areselected among those available in the wild, their trade routes, and potentialconservation impacts. We conducted a large-scale survey in Peru and southernEcuador to simultaneously estimate the relative abundance of parrots in thewild and as household pets in rural areas, determine their origin (locally poa-ched or bought at city markets), and measured the shortest distances to theirnative ranges and markets through the existing grid of roads. Household-poached native parrots were found in 96% of the rural localities surveyed. Mostpets were locally poached, with only 14% of them bought at markets. Parrotpoaching was highly selective, with preferred species (mainly Amazon parrotsand large macaws) being collected much more than expected given their abun-dances in the wild and attaining higher prices than the other species. Individ-uals that were moved away from their native ranges or bought at distantmarkets were of those species most preferred by people, and covered large dis-tances (up to 1010 km), even crossing country boundaries. Our results differfrom those previously obtained from city markets and seizures of illegallytraded parrots in Peru, where preferred species were underrepresented. Localpoaching and rural trade activities act at very large spatial scales and nega-tively affect the population trends of preferred parrot species. This unsustain-able scenario is a challenge to the application of effective conservation actionsaimed at halting poaching and illegal trade. These actions should focus on veryextensive and remote rural areas throughout the Neotropics rather than juston well-known markets located in large cities.